Computational design of binding proteins to EGFR domain II. - Yoon Sup Choi; Soomin Yoon; Kyung-Lock Kim; Jiho Yoo; Parkyong Song; Minsoo Kim; Young-Eun Shin; Won Jun Yang; Jung-eun Noh; Hyun-Soo Cho; Sanguk Kim; Junho Chung; et al. (PLoS ONE, 2014)
We developed a process to produce novel interactions between two previously unrelated proteins. This process selects protein scaffolds and designs protein interfaces that bind to a surface patch of interest on a target protein. Scaffolds with shapes complementary to the target surface patch were screened using an exhaustive computational search of the human proteome and optimized by directed evolution using phage display. This method was applied to successfully design scaffolds that bind to epidermal growth factor receptor (EGFR) domain II, the interface of EGFR dimerization, with high reactivity toward the target surface patch of EGFR domain II. One potential application of these tailor-made protein interactions is the development of therapeutic agents against specific protein targets.